Pengaruh Asap Rokok Terhadap Kadar C-Reactive Protein (CRP) - Zulaikhah, Siti Thomas (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
Smoking is a source of free radicals associated with DNA damage, and as the cause of various diseases. Smoking is a major risk factor for inflammation that can be measured by levels of C-Reactive Protein (CRP). High levels of free radicals can trigger the emergence of Reactive Oxygen Species (ROS). This condition can affect inflammatory mediators in the body, and trigger an inflammatory process characterized by increased levels of C-reactive protein (CRP). CRP can be used as an instrument to monitor the risk of cardiovascular disease complications in active smokers. The purpose of this study was to find out the impact of cigarette smoke exposure on CRP levels in wistar strain rats exposed to cigarette smoke. Design used is experimental with posttest only control group design. The independent variable in the study was exposure to cigarette smoke, while the variables were bound to CRP levels. The study population is male wistar strain rats adapted in inter university research/ Penelitian Antar Universitas (PAU) Universitas Gajah Mada Yogyakarta. Twelve male rats used in the study were randomly divided into 2 groups, group K1 (fed standard food et libitum + aquadest); K2 (fed standard food et libitum + aquadest + cigarette smoke exposure 3 buds/day). Treatments were given for 14 days. Day 15 rats blood are drawn to be checked for CRP levels using ELISA(Enzyme-Linked Immunosorbent Assay), data analyzed using the independent t- test. Mean CRP levels for K1: 3.2Â±0,28 mmol/L and K2:0, 56Â±0,06 mmol/L;. The results of the analysis obtained the p value: 0,000(